Agile methods as stress management tools? An empirical study - Pfeiffer, Sabine; Sauer, Stefan; Ritter, Tobias (Work Organisation, Labour & Globalisation, 2019)
Project-based work is considered a prototype for modern knowledge work, but is also often linked to stress. Complementing or substituting for conventional project management, agile methods are on the rise, but the implications of these methods for stress on employees still remain largely hidden. This article presents the results from qualitative case studies in software development that show how diverse agile methods are lived in practice and how these variations affect stress levels. The results unveil how agile methods, under certain assumptions, can protect team members against stress and voluntary self-exploitation - offering a safe space that is, however, fragile and requires accompanying organisational backing.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Agility; IT professionals; Project work; Scrum; Software engineering; Stress

Agile Projektarbeit in Japan - Sauer, Stefan; Nicklich, Manuel (Computer und Arbeit, 2019)

Agilität als (trans-)lokales Prinzip projektbasierter Arbeit? – Bedingungen und Prozesse prekärer Selbstorganisation - Nicklich, Manuel; Sauer, Stefan (Arbeits- und Industriesoziologische Studien, 2019)
Agile Methoden wie Scrum können als Versuch einer räumlichen Teamzentrierung interpretiert werden, bei der – so unsere Ausgangsbeobachtung – die Lokalität des Teams als besonderer Status selbstorganisierter Arbeit ausgewiesen wird. Demgegenüber gibt es in der Praxis aufgrund dynamischer Organisation der Wertschöpfung zunehmend Ansätze zur Translokalisierung agil arbeitender Teams. Wir rücken daher die Frage, inwiefern agile Projektarbeit unter Bedingungen translokaler Organisation praktiziert wird, in den Mittelpunkt unseres Beitrags. Anhand von zwei Fallstudien in einem Großkonzern und einem KMU aus der Softwareentwicklung vergleichen wir die Unterschiede konkreter Projektarbeit unter lokalen und translokalen Bedingungen und zeigen die Auswirkungen der Translokalisierung auf (Zusammen-)Arbeit und die ‚prekäre Selbstorganisation‘ agiler Teams auf. Unsere Ergebnisse zeigen, dass durch die Translokalisierung der Arbeit die Prozess- und Gegenstandsbezogenheit als zentraler Bestandteil agiler Selbstorganisation prekär werden. In den Unternehmen entwickeln sich im Angesicht dieser Herausforderungen analoge wie digitale Strategien, welche als Versuche zur Substitution von Lokalität betrachtet werden können.<br

Antecedents and consequences of agility: On the ongoing invocation of self-organization - Nicklich, Manuel; Sauer, Stefan; Pfeiffer, Sabine (The Agile Imperative: Teams, Organizations and Society under Reconstruction?, 2021)
By examining theoretical developments, this chapter shows that new concepts such as agility are necessary to revitalize the discussion concerning the participation of employees and the self-organization of teams. It seems that scholars have discussed aspects such as employee participation and self-organization in a similar way for decades. Providing both conceptual and empirical insights, we argue that agile approaches are at risk of missing their goal despite this continuous discussion. This is not least because of their focus on a team-based level without challenging bureaucratic organization and hierarchical leadership as a whole. The text illustrates that agile work needs organizations and employees that are capable of self-organization but cannot tolerate it, since control and inhuman demands are part of its inherent logic.<br

Applaus als Lohn – Lohnerhöhung als Dreistigkeit? - Sauer, Stefan (MAKROSKOP, 2020)

Arbeit: Projektbasiert, selbstorganisiert, wertgeschätzt? - Albert, Bruno; Sauer, Stefan (2024)
Projektarbeit ist – zumindest theoretisch – mit einem erhöhten Maß an Selbstorganisation verbunden und bietet die Möglichkeit (stärker) wertgeschätzter Arbeit. Dieser These gehen wir anhand einer quantitativen Befragung von über 1000 Beschäftigten aus dem Engineering in neun deutschen Maschinenbauunternehmen auf den Grund. Eine multivariate Regressionsanalyse zeigt, dass erhöhte Selbstorganisation auf Teamebene zu mehr wahrgenommener Wertschätzung bei den Beschäftigten führt. Dabei ist zwischen ‚gelebter‘ und lediglich ‚vordergründiger‘ Selbstorganisation zu unterscheiden; nur die gelebte beinhaltet tatsächliche Verfügungsgewalt der Projektteams über Ressourcen und Aufgaben. Gelebte Selbstorganisation hat einen stärkeren positiven Effekt auf die wahrgenommene Wertschätzung als vordergründige Selbstorganisation. Neben der Selbstorganisation haben auch die Dauer der Betriebszugehörigkeit, das Qualifikationsniveau sowie das Geschlecht der Beschäftigten einen signifikanten Einfluss auf die wahrgenommene Wertschätzung. Grundsätzlich lässt sich feststellen, dass sich die von uns untersuchten Betriebe der teambasierten Selbstorganisation nur zögerlich nähern und sogenannte Selbstorganisation stark fremdorganisiert ausgestaltet is
Keywords: Selbstorganisation; Wertschätzung; Agilität; Projektarbeit; Anerkennung

Arbeitssoziologische Belastungsforschung zu neuen Arbeitsformen - Huchler, Norbert; Porschen-Hueck, Stephanie; Ritter, Tobias; Sauer, Stefan (Arbeit und Psyche. Grundlagen, Therapie, Rehabilitation, Prävention - Ein Handbuch, 2018)

Beyond Home or Office – Arbeits(t)raum Homeoffice während und nach Corona. - Schreyer, Jasmin; Sauer, Stefan; Tihlarik, Amelie; Nicklich, Manuel; Pfeiffer, Sabine; Blank, Marco (WSI-Mitteilungen, 2023)
Homeoffice wird im sozialwissenschaftlichen wie medialen Diskurs um die pandemiebedingt veränderte Arbeitswelt meist auf drei Aspekte verkürzt: Erstens gilt die Leistung der Beschäftigten bei der Bewältigung der Pandemie als sekundär. Zweitens sei nicht davon auszugehen, dass nach der Pandemie nur im Homeoffice, sondern im Hybrid-Office gearbeitet werde. Und drittens werde sich der Arbeitsmodus post-pandemisch von einer möglichst vollständigen Kontaktvermeidung wieder hin zu direkter Interaktion intensivieren. Nicht ausschließlich Homeoffice gestaltet die veränderte Arbeitswelt, sondern ein Kontinuum der Arbeit zwischen Präsenz und Nicht-Präsenz. Mittels einer qualitativen Panelbefragung von Führungskräften mit Personalverantwortung aus verschiedenen Branchen wird der Umgang mit der Pandemie seit dem ersten Lockdown reflektiert. Trotz aller Unterschiedlichkeit in den Bewältigungsmodi zeigen sich Gemeinsamkeiten: Wo Homeoffice für Führungskräfte möglich wurde, zeigt sich selbstorganisierte Mehrarbeit im Zuge einer zunehmenden Verschmelzung von Arbeit- und Privatleben ; wo Beschäftigte sachlich bedingt in Präsenz blieben, ihre Führungskräfte jedoch häufig im Homeoffice waren, verstärkte dies erlebte Ungleichheit.<br

Changes in values: Evaluating opportunities for women’s changes of female empowerment in software development - Sauer, Stefan (Journal of International Women's Studies, 2021)
The discrimination of women within the labor market has a vertical as well as a horizontal dimension. These dimensions culminate in the problem of highly skilled jobs within the technical sector. The proportion of women amongst employees and students in this area is very limited, the reasons for this often being old-fashioned bureaucratic structures and a hierarchical corporate culture. Despite these forms of organization, agile frameworks, which are becoming increasingly popular and important, especially within software development, are setting the benchmark for team-based structures as well as a corporate culture based on communication and cooperation. The research questions posed are therefore whether agile frameworks could be used to increase the attractiveness of jobs within the software development sector for women as well as to increase opportunities for women`s empowerment within this sector. To answer these questions briefly, this paper focuses on new agile management roles as well as on women software developers in several European countries. Therefore, we will see that there are opportunities for empowering women but there is also – once again – a risk of gender stereotyping.
Keywords: female empowerment; digitization; gender roles; labor; software development; agile management

Dealing with paradoxes of agile project management. Team-based self-organization between promises and challenges - Sauer, Stefan; Nicklich, Manuel (Journal of Academy of Business and Economics, 2018)

Der relationale Charakter von „digitaler Souveränität“. Zum Umgang mit dem „Autonomie/Heteronomie“-Dilemma in sich transformierenden Arbeitswelten - Sauer, Stefan; Staples, Ronald; Steinbach, Vincent (Was heißt digitale Souveränität? Diskurse, Praktiken und Voraussetzungen „individueller“ und „staatlicher Souveränität“ im digitalen Zeitalter, 2022)

Die Paradoxien von Selbstorganisation und Anerkennung – am Beispiel Agilität - Sauer, Stefan (Agilität? Herausforderungen neuer Konzepte der Selbstorganisation, 2020)

Digitalisierung – Die erste Revolution, die ausgerufen wurde - Sauer, Stefan (MAKROSKOP, 2020)

Empowerment and beyond: Paradoxes of self-organised work - Sauer, Stefan; Nicklich, Manuel (Work Organisation, Labour & Globalisation, 2021)
In recent years, empowerment has increasingly become the watchword for work in knowledge-intensive industries. In particular, The Agile Manifesto (2001) and new management approaches such as agile frameworks promise to cut down documentation duties and increase autonomy for knowledge workers. It nonetheless remains an open question whether self-organisation as a structural framework and self-organising as an agentic, team-based process can actually be realised in a holistic manner. By building on insights into the paradox of organising and the paradox of autonomy and control, we consider the conditions under which self-organised work in fact becomes feasible. We therefore focus conceptually on two paradoxes of empowerment and empirically on project teams within software development firms. Our data show that organisations might respond to these paradoxes by structurally and culturally opening up to agile approaches – thereby not only empowering teams, but also enabling them to develop by providing structural and personal resources, qualifications and means for promoting self-awarenes
Keywords: agile work; autonomy and control; knowledge work; paradox; project-based work; self-organisation

„E-Public Sociology“ als kritische soziologische Intervention? - Nicklich, Manuel; Sauer, Stefan (Momentum Quarterly, 2021)
Die Soziologie spielt im Vergleich zur Betriebswirtschaft, Volkswirtschaft und neuerdings auch Virologie im öffentlichen Diskurs eine vergleichsweise untergeordnete Rolle. Letztlich lassen sich dabei zwei Paradoxien entfalten: Die Soziologie (a) spielt in gesellschaftlichen Diskursen häufig keine Rolle, obwohl sie hierzu prädestiniert sein müsste, und (b) wenn doch, wird ihr Blick besondert. Im Zusammenhang mit der Debatte zur öffentlichen Soziologie bildet sich mittels digitaler Möglichkeiten die „E-Public Sociology“ heraus, die eine beinahe voraussetzungslose Kommunikation mit der interessierten Öffentlichkeit annimmt. Im vorliegenden Text entwickeln wir ein Vier-Felder-Schema zur Analyse soziologischen Wirkens in der Öffentlichkeit und ein darauf fußendes Kommunikationskonzept als Teil der „E-Public Sociology“. Exemplarisch für die sich durch Digitalisierung neu ergebenden Kommunikationsmöglichkeiten fokussieren wir Podcasts als spezifische Form soziologischer Tätigkeit zwischen ‚öffentlicher Soziologie‘ und ‚Soziologie in der Öffentlichkeit‘. Dabei zeigt sich, dass zur Intervention Systematischeres als die bloße Steigerung der Präsenz der Soziologie gefordert ist.<br
Keywords: Kritische Theorie; öffentliche Soziologie; Podcasts; Zeitdiagnose

Erfahrungsbasiertes Kontextwissen als Schlüsselfaktor von Ingenieursarbeit - Sauer, Stefan; Bolte, Annegret (2018)

Erfahrungsbasiertes Kontextwissen: Der Blick aufs Ganze in der technischen Planung - Sauer, Stefan; Bolte, Annegret (Lernen in der Arbeit, 2021)

Erfahrungsbasiertes Kontextwissen in wissensintensiven Tätigkeiten am Beispiel teambasiert arbeitender junger Ingenieurinnen - Sauer, Stefan; Böhle, Fritz; Bolte, Annegret (Arbeit: Zeitschrift für Arbeitsforschung, Arbeitsgestaltung und Arbeitspolitik, 2018)
Junge IngenieurInnen benötigen nicht nur Erfahrungswissen über die Tätigkeiten ihres Teams oder ihrer Abteilung. Sie brauchen auch erfahrungsbasiertes Wissen über Tätigkeiten und Vorgehenslogiken anderer Unternehmensbereiche. Das gilt vor allem im Betriebsmittelbau, der eine Brücke zwischen Produktentwicklung und Fertigung bildet. Um dieses Wissen erwerben zu können, sind Kooperationen über das Team bzw.die Abteilung hinaus erforderlich, die jedoch in der Praxis meist nicht gefördert, oft eher behindert werden. Der Beitrag entwickelt anhand einer empirischen Studie mit jungen IngenieurInnen im Betriebsmittelbau eines Automobil-Großkonzerns das Konzept des erfahrungsbasierten Kontextwissens für dieses Wissens- und Lernziel. Er unterscheidet gegenstandsbezogenes und kooperationsbezogenes Kontextwissen in jeweils vier Dimensionen: Produkt, Prozess, Kultur und Soziales.<br

Erfahrungsbasiertes Kontextwissen: Organisationale Grenzen unterwandern statt überschreiten - Sauer, Stefan; Bolte, Annegret (Grenzüberschreitungen im Kompetenzmanagement : Trends und Entwicklungsperspektiven, 2020)

Erfahrungswissen und lernförderliche Arbeit – Neue Herausforderungen und Perspektiven für Arbeit 4.0 und (Weiter-) Bildung - Sauer, Stefan; Böhle, Fritz (Bildung 2.1 für Arbeit 4.0?, 2019)

From Academic Theory to Management Jargon: Exploring the Evolution and Ideology of the Concept of Mindset. - Blank, Marco; Nicklich, Manuel; Pfeiffer, Sabine; Sauer, Stefan; Tihlarik, Amelie (2023)
In this paper, we investigate the term ‘mindset’, which is increasingly being used in business contexts in the German-speaking world. We explore both its theoretical origins and the current discourse around it in academic and trade publications. In conclusion, we present a tentative critique of the ideology underpinning the concept of mindset.<br

From Agile Teams and Organizations to Agile Business Ecosystems? Contradiction Management as a Requirement of Agile Scaling and Transformation. - Porschen-Hueck, Stephanie; Sauer, Stefan (The Agile Imperative. Teams, Organizations and Society under Reconstruction?, 2021)
New management approaches emerging in the discussion about work 4.0 are closely linked to the debates about VUCA and agility. Agile frameworks are quite successful and the call for an “agile organization” is meanwhile heard virtually everywhere. An important step on the way to agile organizations is on the one hand seen in “Agile Scaling”—the transfer of agile approaches from isolated teams to the organization as a whole. On the other hand, companies increasingly try to actively create their “business ecosystem”. Both agile ideas provide changes and risks for all stakeholders and are challenged by historically grown bureaucratic and hierarchical structures. This chapter argues that active management of contradictions is necessary and provides insights into core principles for agile management of contradictions.<br

Identitätspolitik und der neue Geist des Non-Konformismus - Sauer, Stefan (2020)

Impact of municipal waste recycling and renewable energy consumption on co2 emissions across the european union (Eu) member countries - Bayar, Yilmaz; Gavriletea, Marius Dan; Sauer, Stefan; Paun, Dragos (Sustainability, 2021)
The world population maintains a growing trend and in turn, the amount of municipal waste is also increasing. Rising municipal waste quantity poses a challenge for human beings and the environment, therefore recycling becomes important for environmental sustainability and circular economy. This study explores the effects of municipal waste recycling and renewable energy on the environment sustainability proxied by CO2 emissions in EU member states over the period from 2004 to 2017 through panel cointegration and causality analyses. Recycling is considered an efficient way to reduce CO2 emission, but surprisingly our results indicate mixed findings. The causality analysis revealed no significant interaction among recycling rate, renewable energy and CO2 emissions. However, in the long run, the negative impact of recycling and renewable energy use on CO2 emissions were revealed but varied among the countries. Results indicate that increasing renewable energy consumption will play a significant role in reducing greenhouse gas emissions. These findings must raise awareness among policymakers that should focus on the adoption and implementation of different types of sustainable energy policies that can affect directly or indirectly renewable energy sector development.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CO; Municipal waste recycling; Panel cointegration and causality analyses; Renewable energy

Innovation meets Agility - Four ideal types of a combination of agility and innovation - Sauer, Stefan; Pfeiffer, Sabine (International Journal of Strategic Management, 2018)

Interventionsorientierte Fallstudienforschung – Überlegungen zu Methoden und Realisierung. - Sauer, Stefan; Bolte, Annegret (Lernen in der Arbeit., 2021)

Is the scrum board feminine? - Sauer, Stefan; Tihlarik, Amelie (The Gender of Things, 2023)
The Scrum board plays a vital role in empowering team-based work: agile teams use it to discuss, plan, and estimate their tasks and coordinate these on a daily basis as required. This chapter examines whether the Scrum board can be seen as a feminine tool. Is it a tool by means of which female empowerment is or can be materialized? Does it contribute to creating more gender equity in the world of work? In pursuing these questions, aspects of technocentrism, hierarchies, cooperation and emotions, and bureaucracy are analysed in the light of previous feminist research on the Scrum board, as well as the Agile Manifesto and its approach<br
CRIS-Team Scopus Importer:2024-12-16

Kompetenzen für die Gestaltung von Arbeit in der Planung und Entwicklung - Heidling, Eckhard; Sauer, Stefan; Böhle, Fritz; Bolte, Annegret; Neumer, Judith (Gestaltungskompetenzen für gesundes Arbeiten. Arbeitsgestaltung im Zeitalter der Digitalisierung, 2018)

Kompetenzen für Innovationsarbeit in der Offenen Organisation: Management und Aneignung - Porschen-Hueck, Stephanie; Huchler, Norbert; Sauer, Stefan; Krakowski, Christian; Streit, Tatjana; Müller-Kreiner, Claudia (Vernetztes Kompetenzmanagement. Reihe Kompetenzmanagement in Organisationen, 2018)

Labouratory: Making Work and Digitalization participatory – instead of discoursively playing them off against one other. - Sauer, Stefan; Blank, Marco; Pfeiffer, Sabine (Journal of International Management Studies, 2021)
Digitalization is often thought about only in terms of technical possibilities; the feasibility of its implementation in labor processes and the needs of the latter are given little attention. In our Labouratory, we want to invert this process: to place the focus on the needs of human labor and, with this as point of departure, to ask where and how digitalization can best support and facilitate labor processes.<br
Keywords: digitalization; digitalized labor; labor processes; participatory research; mixed methods

Lernförderlichkeit bei wissensintensiven Tätigkeiten. Neue Herausforderungen und Perspektiven - Sauer, Stefan; Neumer, Judith; Buschmeyer, Jost (Berufsbildung in Wissenschaft und Praxis, 2018)

Mindset - Begriffskarriere zwischen Management-Talk, Wissenschaft und Ideologie. Eine explorative Annäherung - Blank, Marco; Held, Maximilian; Nicklich, Manuel; Pfeiffer, Sabine; Sauer, Stefan; Tihlarik, Amelie (2020)
Der Text beschäftigt sich mit dem im Unternehmenskontext an Bedeutung gewinnenden Begriff Mindset. Es wird einerseits den theoretischen Ursprüngen nachgegangen und andererseits der aktuelle Diskurs in wissenschaftlichen und sich an die Fachpraxis richtenden Publikationen aufgearbeitet. Verschiedene empirische Wege-mehrere Webrecherchen mit unterschiedlichen Zugriffen, qualitative Sekundäranalysen, Webmining und Expert*innen-Interviews-nähern sich diesem empirischen Phänomen und versuchen sich an einer Unterscheidung zwischen reinem Anglizismus, klaren Definitionen und im Betrieb teils wirksamen Folgen (bspw. wenn das Mindset von Beschäftigten vermessen wird). Abschließend wird eine tentative, ideologiekritische Einordnung angeboten. <br

New management approaches in digitized work as the cure for inequality? - Tihlarik, Amelie; Sauer, Stefan (Social Sciences, 2021)
Due to the increasing importance of digitization, ICT and engineering sectors are also growing. In these sectors, there are a lot of high-qualified and well-paid jobs. However, despite the growing importance and popularity of digital solutions, one fact (at least) is, unfortunately, still very stable within the ICT and engineering sectors: When it comes to employees, there are still huge differences with respect to gender and gender stereotypes. (Commercial) technology development can be regarded as having masculine connotations both structurally and culturally. Therefore, we address these connotations, especially the roles of androcentric bureaucracy, which could be described as hierarchical, technocentric, and very controlling-oriented, and (the structural possibilities of) self-efficacy. We discuss, conceptually and empirically with a focus on software development, whether new management approaches like agile frameworks and new management roles like Feel-good Managers and Scrum Master could be seen as a cure for inequality or if there are new stereotypical gender-related ascriptions for specific activities or processes.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Agile management; Digitization; Engineering; Feel-good management; Female empowerment; Gender inequality; ICT; New management approaches; Project management

New Software Development Methodologies between Diversity and Gender Stereotypes - Sauer, Stefan; Tihlarik, Amelie (Review of Business Research, 2020)
Based on the diagnosis of new software development methodologies, this paper examines the research question, if these new approaches are leading towards more diversity regarding this strongly masculine dominated field or if they foster the reproduction of gender stereotypes in a new way. Therefore, we suggest a five step analytical concept. We examine the roles of feel-good management as well as persons in charge of agile processes empirically referring to our research question.<br
Keywords: diversity; labour and gender; project management; agile project management; gender stereotypes

Pelzindustrie – Ein Ende mit Schrecken oder Schrecken ohne Ende? - Sauer, Stefan (MAKROSKOP, 2022)

Perspectives on agile management and agile organization - Sauer, Stefan (International Journal of Strategic Management, 2018)

Pflege-Krise: Ressentiments statt Reform? - Sauer, Stefan (MAKROSKOP, 2021)

Project Management between Project Leadership and Project Support - Sauer, Stefan (Journal of International Management Studies, 2018)

Projektarbeit: Potenziale und Risiken der „schönen neuen Arbeitswelt“ - Sauer, Stefan (Berliner Debatte Initial : sozial- und geisteswissenschaftliches Journal, 2021)

Projekt, Projektarbeit, Projektmanagement - Sauer, Stefan (Lexikon der Arbeits- und Industriesoziologie, 2023)

Qualitative Interviews auf Distanz - Das Interview im Zeitalter seiner virtuellen Durchführbarkeit - Nicklich, Manuel; Röbenack, Silke; Sauer, Stefan; Schreyer, Jasmin; Tihlarik, Amelie (Forum qualitative Sozialforschung, 2023)
Due to the coronavirus pandemic, the practice of qualitative interviewing has recently undergone a strong trend toward virtualization. The gold standard of conducting face-to-face interviews had to be translated into a digital format, enabling researchers to conduct interviews at a distance. In this article, we reflect on the opportunities and limitations of virtual interviews and consider epistemological consequences in the wake of their increased use and acceptance. Methodological questions arise regarding empirical topics, sampling, social interview situations, as well as the technical setting. We further reflect on the advantages and disadvantages of interviews at a distance and suggest that this novel form of interviewing may soon become the new normal</em
Keywords: digitalization; virtual interviews; coronavirus pandemic

Qualitative Sozialforschung auf Distanz. Das Interview im Zeitalter seiner virtuellen Durchführbarkeit - Nicklich, Manuel; Röbenack, Silke; Sauer, Stefan; Schreyer, Jasmin; Tihlarik, Amelie (Forum qualitative Sozialforschung, 2023)
CRIS-Team Scopus Importer:2023-03-03

Reflexive scaling as a way towards agile organizations - Neumer, Judith; Porschen-Hueck, Stephanie; Sauer, Stefan (Journal of International Management Studies, 2018)

Rettung eines Relikts - Sauer, Stefan (MAKROSKOP, 2020)

Schulen zu, Büros offen? Der mühsame Weg zum Homeoffice - Sauer, Stefan (MAKROSKOP, 2021)

Socio-ecological sustainability @work - Sauer, Stefan; Blank, Marco (European Journal of Management, 2019)
In order to achieve climate goals, it is becoming increasingly necessary to involve industry, to the extent that people are taking to the streets to put the pressure on both politicians and industry. This shows not only the urgent need for action, but also the rise in climate change awareness in recent years. We do not ask what has triggered this; rather we demonstrate that there is a powerhouse available for CO2 reduction which has not been used hitherto. One of the main measures for reducing CO2 in industry is the implementation of specialist units. Although the idea to put specialists in place in order to solve an issue is understandable, it is not quite that easy. Often, the specialists have a large toolkit at their disposal, but do not know where to use it. Therefore a lot of their measures only scratch the surface while employees, who are often much more aware of what could be done because of their tacit knowledge, could provide more efficient solutions. In this paper, we demonstrate that a lot of employees are already familiar with productive use and environmental protection. Not because of training or workshops, but because they inherit climate change as an ethical concept in their daily lives. If our approach is taken seriously, the demand for environmental sustainability will also lead to empowerment of employees and social sustainability.<br
Keywords: sustainability; environment; productive use; eco-self; self-organization; empowerment; labour

Soziologische Perspektiven auf Arbeit 4.0 - Huchler, Norbert; Sauer, Stefan (Arbeit 4.0 aktiv gestalten. Die Zukunft der Arbeit zwischen Agilität, People Analytics und Digitalisierung, 2018)

Soziologische Perspektiven auf Arbeit 4.0 - Sauer, Stefan; Huchler, Norbert (Arbeit 4.0 aktiv gestalten. Die Zukunft der Arbeit zwischen Agilität, People Analytics und Digitalisierung, 2018)

Subjektivierendes Arbeitshandeln und Anerkennung als konzeptioneller Rahmen für die Analyse von tätigkeits- und kontextbezogenem Erfahrungswissen - Bolte, Annegret; Sauer, Stefan (Lernen in der Arbeit, 2021)

Subjektivierung der Arbeit in a Nutshell. Die Be-Arbeitung der Corona-Krise. - Schreyer, Jasmin; Pfeiffer, Sabine; Sauer, Stefan; Nicklich, Manuel; Blank, Marco; Tihlarik, Amelie (Arbeit: Zeitschrift für Arbeitsforschung, Arbeitsgestaltung und Arbeitspolitik, 2022)
Im sozialwissenschaftlichen Diskurs und den medialen Debatten wird die Covid-19-Pandemie zunehmend als disruptive Kraft in Bezug auf die Digitalisierung der Arbeitswelt wahrgenommen. Während dabei vor allem die Möglichkeit von Homeoffice thematisiert wird, steht im Zentrum unseres Artikels die situative Be-Arbeitung dieses Wandels durch die Beschäftigten im Zuge betrieblicher Reorganisation – mit seinen sichtbaren mittel- und ggf. langfristigen Folgen für die zukünftige Gestaltung von Arbeit. Der Beitrag zeichnet diese Zusammenhänge anhand eines qualitativen Panels nach: Seit dem ersten Lockdown wurden wiederholt Interviews mit Führungskräften unterschiedlicher Branchen geführt, um ihre laufend reflektierten Perspektiven zu erheben. Dabei zeigt sich: Einerseits greift Subjektivierung als struktureller Prozess des instrumentellen Zugriffs der Organisation auf Subjektpotenziale und damit auf den ganzen Menschen ins Leere. Andererseits ermöglicht die Subjektivierung von Arbeit als spontaner und selbstorganisierter Prozess erst die erfolgreiche Be-Arbeitung der Herausforderungen durch die Pandemie. Sichtbar wird in der Pandemie eine Art ‚Kontingenzkompetenz‘ der Beschäftigten, die im Nachgang von den Unternehmen wieder integriert und zur Erwartung im Sinne einer strukturellen Subjektivierung werden könnte.<br
Keywords: Digitalisierung; Disruption; Subjektivierung; Selbstorganisation; organisationale Reorganisation; Covid-19

Talking agile, talking digital - Sauer, Stefan (Computer und Arbeit, 2019)

The Agile Imperative: A Multi-Level Perspective on Agility as a New Principle of Organizing Work. - Sauer, Stefan; Nicklich, Manuel; Pfeiffer, Sabine (The Agile Imperative: Teams, Organizations and Society under Reconstruction?, 2021)
This introductory chapter presents the scope of the book and summarises its main theme, the role of commercial banks in supplying inside money with loans to the economy in addition to outside money. The focus is on the relevant agents that compose a monetary system along with updated data, for example on the saving ratio.<br

The Agile Imperative: Teams, Organizations and Society under Reconstruction? - Pfeiffer, Sabine; Nicklich, Manuel; Sauer, Stefan (Palgrave McMillan., 2021)
In an ever-changing working environment, customer and workplace demands have brought new challenges to how we organize and manage work. Increasingly, this is addressed by the idea of 'agility.' From its beginning, agile work has claimed to be a radically different approach which allows organisations to react flexibly to changing environmental demands whilst also offering a ‘people' centered approach to management. While the literature often examines agile instruments from a business perspective, this edited collection advances the discussion of the efficacy of agile working, by applying a more critical social science perspective.The chapters scrutinize whether agility is just a discursive imperative, or an organizational and institutional reaction to better deal with complexity and volatility. The answers to these questions can vary at different levels, and the editors therefore examine agility at the level of teams, organizations and societies. By assembling different perspectives on the sustainability and virtue of agile instruments, and bringing together international scholars and different disciplines, which bring in different - sometimes contrary and more or less controversial views - on agile work, the project stimulates a comparative discussion.
Keywords: New principles of organizing work; Project management; Agile work; Self-Organization; Autonomy; Design Thinking; New Work; Empowerment

Zukunftsszenarien der Arbeit. Diskursive Versprechen, gelebte Realitäten und das Gespenst der Regression - Sauer, Stefan; Nicklich, Manuel (Momentum Quarterly, 2022)
Der Diskurs rund um Digitalisierung hat sich – so unsere Ausgangsdiagnose – von der erfahrbaren Realität (nicht nur) in der Arbeitswelt abgekoppelt. Es dominieren wolkige Versprechungen in Zusammenhang mit neuen Arbeitsformen einerseits und Drohszenarien von der massenhaften Substitution menschlicher Arbeit andererseits. Dies birgt, wie wir unter Rückgriff auf Gedanken der Kritischen Theorie und insbesondere von Erich Fromm ausführen, die Gefahren einer Regression im Sinne einer Hinwendung an ‚alte‘ Autoritätsfiguren oder eines fatalistischen Solutionismus. Als Alternative hierzu schlagen wir eine auf Erfahrung basierende Auseinandersetzung mit digitalen Unterstützungsmöglichkeiten für menschliche Arbeitstätigkeiten vo
Keywords: Digitalisierung; Arbeit; Innovation; Kritische Theorie